Surgical technique to achieve postoperative alar base symmetry in complete bilateral cleft lip and alveolus repair - A prospective study - K S Krishna Kumar; Shermil Sayd; Suresh Vyloppilli; Santhy Mohanachandran Nair; Ajit Pati; Anand Sivadasan (Wolters Kluwer Medknow Publications, 2023)
Introduction: Children born with the bilateral cleft lip-cleft palate have a shortened columella and an elevated protruding premaxilla which results in an abnormal appearance of the nose. Materials and Methods: This study was conducted in the Baby MemorialHospital, Calicut, a Smile Train Center in India. After scrutiny, the eligible sample size amounted to30 cases. The patient's age rangedfrom 4 to 7 months. The basic technique employed is "Veau three straight line repair" technique. This study analyses the importance of a geometrical incision, a back cut extending cephalically above the inferior turbinate at the mucocutaneous junction to elevate the nostril floor, to achieve the symmetry of the alar bases. Result: Preoperative and postoperative anthropometric studies were conducted on the asymmetry and symmetry of the alar bases. The p values for the right side preoperative and postoperative measurement is 0.007 which is highly significant and for the left side, it is <0.001 which also denotes statistical significance of this technique. Conclusion: Further high volume multicentric studies may be suggested since bilateral cases amount for only 10% of the overall incidence of cleft lip cases and even high volume surgeons are privileged to treat only a few. Therefore, it is the obligation of every surgeon who undertakes the care of these children to learn from the past and to analyse results periodically, including comparison with other centres.